On t í»-t í» - BROZEK, Bartosz (Utopía y Praxis Latinoamericana, 2016)
My goal in this short paper is to argue thatÂ so-called intermediary concepts play an essential roleÂ in organizing and generating legal knowledge. MyÂ point of departure is a reconstruction and a critique ofÂ Alf Ross”™s analysis of such concepts. His goal was toÂ argue that there exist concept in the law which haveÂ no semantic reference, yet it is reasonable to useÂ them as they perform some useful function regardingÂ the presentation of legal rules. I believe that Ross isÂ wrong on both counts: his argument to the effect thatÂ intermediary concepts have no reference is flawed, andÂ his characterization of the functions such concepts playÂ in the law is too limiting.